# Thread: Specific Point of Limit on graph

1. ## Specific Point of Limit on graph

Interpret the limit as the slope of the tangent line to a curve at a specific point after you evaluate the limit.

lim[(1+h)^(1/6)-1]/h
h->0

I evaluated the limit to be
M_t=1/6 to y=x^(1/6) but I am having trouble finding the x co-ordinate.

The answer in the back says:
M_t=1/6 to y=x^(1/6) at x=1

how did they get x=1?

2. Originally Posted by skeske1234
Interpret the limit as the slope of the tangent line to a curve at a specific point after you evaluate the limit.
lim[(1+h)^(1/6)-1]/h
h->0
I evaluated the limit to be
M_t=1/6 to y=x^(1/6) but I am having trouble finding the x co-ordinate.
The answer in the back says:
M_t=1/6 to y=x^(1/6) at x=1
how did they get x=1?
Actually you are given that $\color{red}x=1$.
It is part of the statement of the problem. See above.

3. Originally Posted by skeske1234
Interpret the limit as the slope of the tangent line to a curve at a specific point after you evaluate the limit.

lim[(1+h)^(1/6)-1]/h
h->0

I evaluated the limit to be
M_t=1/6 to y=x^(1/6) but I am having trouble finding the x co-ordinate.

The answer in the back says:
M_t=1/6 to y=x^(1/6) at x=1

how did they get x=1?
If you need evaluate the $\mathop {\lim }\limits_{h \to 0} \frac{{{{\left( {1 + h} \right)}^{1/6}} - 1}}{h}$ then, using the formula for the difference of cubes, we get

${\left( {1 + h} \right)^{1/2}} - 1 = \left( {{{\left( {1 + h} \right)}^{1/6}} - 1} \right)\left( {{{\left( {1 + h} \right)}^{1/3}} + {{\left( {1 + h} \right)}^{1/6}} + 1} \right) \Leftrightarrow$

$\Leftrightarrow {\left( {1 + h} \right)^{1/6}} - 1 = \frac{{{{\left( {1 + h} \right)}^{1/2}} - 1}}{{{{\left( {1 + h} \right)}^{1/3}} + {{\left( {1 + h} \right)}^{1/6}} + 1}}.$

So we have

$\mathop {\lim }\limits_{h \to 0} \frac{{{{\left( {1 + h} \right)}^{1/6}} - 1}}{h} = \mathop {\lim }\limits_{h \to 0} \frac{{{{\left( {1 + h} \right)}^{1/2}} - 1}}{{h\left( {{{\left( {1 + h} \right)}^{1/3}} + {{\left( {1 + h} \right)}^{1/6}} + 1} \right)}} =$

$= \mathop {\lim }\limits_{h \to 0} \frac{{\left( {{{\left( {1 + h} \right)}^{1/2}} - 1} \right)\left( {{{\left( {1 + h} \right)}^{1/2}} + 1} \right)}}{{h\left( {{{\left( {1 + h} \right)}^{1/3}} + {{\left( {1 + h} \right)}^{1/6}} + 1} \right)\left( {{{\left( {1 + h} \right)}^{1/2}} + 1} \right)}} =$

$= \mathop {\lim }\limits_{h \to 0} \frac{1}{{\left( {{{\left( {1 + h} \right)}^{1/3}} + {{\left( {1 + h} \right)}^{1/6}} + 1} \right)\left( {{{\left( {1 + h} \right)}^{1/2}} + 1} \right)}} = \frac{1}{{3 \cdot 2}} = \frac{1}{6}.$

4. Put $t=\sqrt[6]{h+1}$ so that $t\to1$ and $h=t^6-1.$